Age of Onset and Neuropsychological Functioning in Alcohol Dependent Inpatients. (1st October 2012) - Joos, Leen; Schmaal, Lianne; Goudriaan, Anna E.; Fransen, Erik; Van, Wim; Sabbe, Bernard G. C.; Dom, Geert
<x xml:space="preserve">Abstract</x> Background Differences in clinical characteristics between early and late onset alcohol dependent patients have been examined intensively, but little is known about the differences in neuropsychological functioning between these patient groups. Clinical characteristics and neuropsychological functions of inpatients with early onset and late onset alcohol dependence are therefore investigated in this study. Methods Ninety‐three abstinent alcohol dependent inpatients meeting a current diagnosis of DSM‐IV alcohol dependence were divided into early onset alcohol dependent patients (EOA; ≤25 years; n = 36) and late onset alcohol dependent patients (LOA; >25 years; n = 57). Patients using psychoactive medication and patients dependent on other substances than alcohol (and nicotine) were excluded. A comprehensive neuropsychological test battery was administered. Results EOA reported higher trait impulsivity, antisocial traits, and attention deficit hyperactivity disorder‐related traits and exhibited an impulsive reflection style, especially in a high‐risk context, compared with LOA. Against expectations, EOA performed significantly better on measures of planning, cognitive control, visual memory, and delayed recognition memory than LOA, whereas no significant group differences occurred on measures of delay discounting, digit span, and attention. Better Stroop interference, better visual memory, and a more impulsive reflection style was predictive of an early age of onset, and explained a significant and additional amount of variance (18.8%) on top of the clinical characteristics, together explaining 53.4% of the variance. Conclusions Both clinical characteristics and neuropsychological variables contributed independently to the age of onset of problematic alcohol use. Results indicate that especially an impulsive reflection style, besides higher trait impulsivity, may be the core feature of early onset alcohol dependence. However, the contribution of the neuropsychological variables is complex and more research is needed to clarify the role of psychiatric comorbidity and poly‐substance abuse in an unselected sample of alcohol dependent patients.